Circulating tumour cells and circulating cell-free DNA in patients with lung cancer: a comparison between thoracotomy and video-assisted thoracoscopic surgery - Vladimir Anikin; Thomas Carter; Marcia Hall; Andreas Polychronis; Periklis Katopodis; Uday Kishore; Nizar Asadi; Emmanouil Karteris (BMJ Open Respiratory Research)
Introduction The type of lung cancer surgery impacts on tumour manipulation during surgery and may drive dissemination of cancer cells into the vasculature, thus facilitating metastatic spread. The aim of this study was to investigate the impact of surgically induced trauma using peripheral blood from preoperative and postoperative patients with non-small cell lung cancer (NSCLC) undergoing thoracotomy or video-assisted thoracoscopic surgery (VATS) resection.Methods Imaging flow cytometry was used to measure circulating cancer-associated cells (CCs). Circulating cell-free DNA (ccfDNA) isolation was performed using Promega dsDNA HS Assay Kit. DNA integrity measurements were calculated by the ALU247 to ALU115 ratio and cytokine levels measured using the Luminex screening assay.Results CCs were increased in postoperative blood samples in 54 patients with NSCLC. Patients who underwent thoracotomy instead of VATS had higher numbers of EpCAM (p=0.004) and PanCK-labelled (p=0.03) CCs postoperatively. ccfDNA and DNA integrity index were also significantly increased in postoperative samples (p=0.0009 and p=0.04), with concomitant increase in interleukin 6 and interleukin 10 levels in the same cohorts (p=0.0004 and p=0.034, respectively).Conclusions In this study we have shown the potential clinical utility of several biomarkers from liquid biopsies to guide perioperative management, as well as provide a snapshot of the type of surgical resection in terms of circulating tumour cell release. Obtaining reliable readouts from blood can provide crucial information for disease progression, as well as being of prognostic value monitoring patients’ response to treatment.